2008
DOI: 10.1007/s00705-008-0084-z
|View full text |Cite
|
Sign up to set email alerts
|

Different expression patterns of CK2 subunits in the brains of experimental animals and patients with transmissible spongiform encephalopathies

Abstract: To address the possible alteration of casein kinase 2 (CK2) in transmissible spongiform encephalopathies (TSEs), the levels and patterns of CK2 in the brain tissues of hamsters or C57BL mice inoculated intracerebrally with scrapie agents 263K or 139A were evaluated by Western blots, followed by quantitative analysis. Specific semi-quantitative RT-PCR for evaluating the mRNA transcripts of CK2 subunits was performed in parallel. Compared with normal animals, the levels of CK2alpha and CK2beta in the brains of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Beige crystals (43%); mp 70 C. IR (KBr) 3280 (NH), 1690 and 1680 (CO). 1 2 (0.15 mmol) and BINAP (0.225 mmol) in 15 mL of toluene was heated at 100 C for 20 h. The reaction mixture was allowed to cool to room temperature, diluted with dichloromethane and filtered through a pad of Celite and the filter cake was washed with dichloromethane (Â3). Concentration and flash chromatography on silica gel using AcOEt/cyclohexane (3/7, v/v) To suspension of 4-bromopyrrole-1,2-dicarboxylic acid 1-tertbutyl ester 2-methyl ester (21) (10 mmol), and Pd(PPh 3 ) 4 (0.5 mmol) in a mixture of toluene/EtOH (120/6 mL) under nitrogen were added K 2 CO 3 (11 mmol) and 3-pyridylboronic acid (11 mmol).…”
Section: Ethyl 3-amino-2-pyrrol-1-ylbenzoate (10)mentioning
confidence: 99%
See 1 more Smart Citation
“…Beige crystals (43%); mp 70 C. IR (KBr) 3280 (NH), 1690 and 1680 (CO). 1 2 (0.15 mmol) and BINAP (0.225 mmol) in 15 mL of toluene was heated at 100 C for 20 h. The reaction mixture was allowed to cool to room temperature, diluted with dichloromethane and filtered through a pad of Celite and the filter cake was washed with dichloromethane (Â3). Concentration and flash chromatography on silica gel using AcOEt/cyclohexane (3/7, v/v) To suspension of 4-bromopyrrole-1,2-dicarboxylic acid 1-tertbutyl ester 2-methyl ester (21) (10 mmol), and Pd(PPh 3 ) 4 (0.5 mmol) in a mixture of toluene/EtOH (120/6 mL) under nitrogen were added K 2 CO 3 (11 mmol) and 3-pyridylboronic acid (11 mmol).…”
Section: Ethyl 3-amino-2-pyrrol-1-ylbenzoate (10)mentioning
confidence: 99%
“…The catalytic subunits of CK2 (alpha and/or alpha 0 ) are constitutively active either alone or in combination with the regulatory beta-subunits to give a heterotetrameric protein. A third isoform of the catalytic subunit, designated CK2a 00 , was discovered more recently [1] and only very limited information is available. Since its discovery in 1954 by Burnett and Kennedy [2], the activity of CK2 in physiological and pathological processes has been largely studied [3e5], particularly in cell proliferation and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that CK2 interacted more strongly with unglycosylated PrP than with its glycosylated forms. Furthermore, changes in the expression pattern of CK2 subunits were observed in the brain of scrapie-infected animals and human TSE cases (Chen et al 2008b). Since CK2 is also an ectokinase found in the extracellular matrix (Canton and Litchfield 2006), it is possible that it may interact not only with cytoPrP or nuclear PrP, but also with PrP C anchored on the plasma membrane.…”
Section: Ck2mentioning
confidence: 96%
“…The clinical and neuropathological characteristics have been described previously [15,16]. The surgical harvests of the brains of infected animals were performed either under euthanasia with intraperitoneal injection of chloral hydrate at the moribund time or postmortem after death.…”
Section: Preparation Of Brain Homogenatesmentioning
confidence: 99%